The age of Calamity time frame AD 1300-1400 - 20160731 frey50 (Time-Life Books Alexandria, Virginia, 1989)
Surveys fourteenth-century world history in the eastern hemisphere
The Hundred Year's War--The Rise of the Ottomans--The fury of the steppes--China's Brilliant dynasty.
Includes bibliographical references and index
Keywords: Fourteenth century; Disasters -- History